2003
DOI: 10.1159/000074262
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Macrosomic, Normal and Intrauterine Growth Retarded Neonates Using the Modified Neonatal Growth Assessment Score

Abstract: Objective: Separation of Macrosomic, normal and intrauterine growth retarded (IUGR) neonates using the modified Neonatal Growth Assessment Score (NGAS). Methods: A sample of 23 neonates with evidence of growth acceleration and 74 neonates classified as normal or IUGR in a previous study was used in this investigation. The prenatal growth of all neonates had been studied longitudinally with ultrasound. From the data collected, Rossavik models describing the growth trajectories of head circumference (HC), abdomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 13 publications
0
42
0
Order By: Relevance
“…In contrast, abdominal circumference and ponderal index were reduced following TPN, suggesting that these animals were exhibiting signs of disproportionate body growth, akin to that observed in intra-uterine growth restricted human pregnancies [56] . The differences seen in organ weight are typical of those previously reported in piglets on TPN [38,39] .…”
Section: Discussionmentioning
confidence: 86%
“…In contrast, abdominal circumference and ponderal index were reduced following TPN, suggesting that these animals were exhibiting signs of disproportionate body growth, akin to that observed in intra-uterine growth restricted human pregnancies [56] . The differences seen in organ weight are typical of those previously reported in piglets on TPN [38,39] .…”
Section: Discussionmentioning
confidence: 86%
“…It is important to note that after the completion of our study, Deter and Spencer reported new criteria for the diagnosis of IUGR that might result in an increase in IUGR fetuses with CHD. 19 Further investigation into the pathophysiology of poor fetal growth in cases of CHD and identification of which defects are most at risk is necessary to determine optimal management of prenatally diagnosed CHD.…”
Section: Discussionmentioning
confidence: 99%
“…Linear discriminant analysis has been used to determine boundaries for separating neonates with normal and abnormal growth outcomes. 37 Normally growing neonates have m 3 NGAS 51 values ranging from 182.5% to 210.0%.…”
Section: Neonatal Growth Outcomesmentioning
confidence: 99%